Formal integrability for monodromic nilpotent singular points in R 3 - Pessoa, Claudio [UNESP]; Queiroz, Lucas [UNESP] (Elsevier, 2025)
Consider analytic three-dimensional differential systems having a singular point at the origin such that its linear part is y ∂ x − λ z ∂ z for some λ ≠ 0 . The restriction of such systems to a center manifold has a nilpotent singular point at the origin. We study the formal and analytic integrability for those types of singular points in the monodromic case. As a byproduct, we obtain some useful results for planar C r systems having a monodromic nilpotent singularity. We conclude the work by studying issues related to monodromy and formal integrability for the Elsonbaty–El-Sayed system, the Hide–Skeldon–Acheson dynamo system and the Generalized Lorenz system. For this last system, we were able to detect nilpotent centers.